Is there an overlapping market between national car producers in Malaysia? - Drebee, Hayder Abbas; Abdul Razak, Nor Azam; Abd Karim, Mohd Zaini (Universiti Kebangsaan Malaysia, 2014)
This paper examines how the choice of three broad categories of automobiles in Malaysia (i.e.Proton, Perodua, and foreign automobiles) is affected by a change in the price of a specific car model. Using a sample of 478 automobile owners in Malaysia, a discrete choice analysis is conducted based on the conditional logit model.In general, it is found that the own-price effect on Proton (Perodua) cars is negatively related to a specific Proton (Perodua) model; in contrast, the cross-price effect on Proton (Perodua) cars is positively related to a specific Perodua (Proton) model. Of the nine models evaluated, three of them show a significant overlapping market segment. This finding implies that Proton and Perodua should differentiate these products further to lessen competition between them.